Lithium iron phosphate material as well as preparation method and application thereof
By in-situ doping high-conductivity carbon source and surface carbon coating during the synthesis of lithium iron phosphate materials, the limitations of lithium iron phosphate materials in terms of magnification and low-temperature discharge performance are solved, and the effects of high compaction density and low carbon content are achieved.
Patent Information
- Application Number
- CN202510100768.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-29
AI Technical Summary
The existing lithium iron phosphate materials have limitations in terms of magnification and low-temperature discharge performance, and the high carbon content limits the improvement of the compaction density of the material.
By doping in situ with a high conductivity carbon source during the synthesis of iron phosphate, the conductivity of iron phosphate itself is improved, and a second carbon coating is performed on the surface of lithium iron phosphate material to reduce the total carbon content to improve compaction density.
The high-rate charge and discharge performance and high compaction density of lithium iron phosphate materials were achieved, the internal resistance of the powder was reduced, the carbon content was reduced to <1.0 wt%, and the compaction density was >3.0g/cm3.
Smart Images

Figure CN119898742A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion technology, and in particular to a lithium iron phosphate material and a preparation method and application thereof. Background Art
[0002] Lithium iron phosphate (LiFePO4) is a commonly used positive electrode material for lithium-ion batteries, and has attracted widespread attention for its high safety, long life and relatively low price. However, lithium iron phosphate itself is a semiconductor, and its electronic conductivity is relatively low compared to lithium nickel cobalt manganese oxide and lithium manganese oxide, and lithium ions are conducted in a one-dimensional direction inside its particles, which greatly limits the rate and low-temperature discharge performance of lithium iron phosphate.
[0003] At present, the main methods to improve the conductivity of lithium iron phosphate are nano-sizing, carbon coating and metal ion doping. The existing mainstream synthesis process steps are: iron phosphate, lithium carbonate, glucose & PEG, and metal dopants are mixed in an aqueous solution, and then ball milled, sand milled, spray dried, and then high-temperature thermal reduction is performed to obtain lithium iron phosphate. Or the steps are: phosphoric acid, iron sulfate, and lithium hydroxide react under hydrothermal conditions to form lithium iron phosphate, and then the lithium iron phosphate is carbon coated to obtain the finished lithium iron phosphate.
[0004] The defects of the existing solutions are: the improvement measures for lithium iron phosphate are generally between the primary particles or on the surface, but cannot improve the electronic and ionic conductivity inside the lithium iron phosphate. The 0.1C discharge can only reach about 160mAh / g, and about 10mAh / g of capacity cannot be used; at the same time, in order to maintain conductivity, the carbon content is generally above 1.2wt%, resulting in the compaction density of lithium iron phosphate powder under 3t pressure reaching only 2.6g / cm 3 The true density of lithium iron phosphate is about 3.4g / cm 3 Therefore, the higher carbon content greatly limits the improvement of the compaction density of lithium iron phosphate.
[0005] A higher compaction density can increase the energy density of the battery because more active materials can be stored in the same volume, thereby increasing the battery capacity. This means that in a battery of the same size, the higher the compaction density, the more electricity can be stored in theory, so while improving the conductivity of lithium iron phosphate, it is also necessary to take into account the compaction density. Summary of the invention
[0006] The object of the present invention is to provide a lithium iron phosphate material with high rate charge and discharge performance and high compaction density; another object of the present invention is to provide a method for preparing a lithium iron phosphate material with high rate charge and discharge performance and high compaction density.
[0007] The present invention discloses a method for preparing a lithium iron phosphate material, comprising the following steps:
[0008] S1: Mix the first iron source, high conductivity carbon source, and phosphoric acid, add an oxidant to remove Fe 2+ Oxidized to Fe 3+ , add a pH regulator to adjust the pH of the reaction solution to 1.2-2.5, and control the temperature at 85-95°C until the reaction is complete;
[0009] S2: maintaining the temperature of the reaction solution at 110-130° C. for aging for 3-5 hours, separating the obtained precipitate, washing, drying, and calcining at 550-700° C. to obtain iron phosphate;
[0010] S3: mixing the iron phosphate, the second carbon source, the lithium source, the second iron source and water to form a mixture; controlling the particle size of solid particles in the mixture to D50 of 200-400 nm by ball milling and sand milling; spray drying the mixture to obtain a solid;
[0011] S4: In a protective gas atmosphere, heat the solid to 730-790°C at a heating rate of 1.5-5°C / min, keep warm for 6-12 hours, and cool to obtain a lithium iron phosphate material.
[0012] The oxidant includes H2O2 and / or sodium hypochlorite.
[0013] In the preparation process of lithium iron phosphate material, the first addition of high conductivity carbon source belongs to bulk doping, which improves the conductivity inside the iron phosphate; the second addition of the second carbon source is to coat the second carbon source on the surface of the lithium iron phosphate material, thereby improving the conductivity of the surface of the lithium iron phosphate material.
[0014] pH adjusters include sodium hydroxide or ammonia.
[0015] Furthermore, in step S1, the first iron source includes one or more of ferrous sulfate, ferric sulfate, elemental iron, and ferric chloride, and the high conductivity carbon source includes one or more of porous nanocarbon, acetylene black, superconducting carbon black, single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), 3D graphene mesh, nanographene sheets, and carbon fibers.
[0016] Furthermore, in step S1, the molar ratio of the iron element in the first iron source to the phosphorus element in the phosphoric acid is 1:(1.0-1.2); the mass ratio of the first iron source to the first carbon source is 1:(0.0005-0.005).
[0017] Furthermore, in step S3, the second carbon source includes two or more of sucrose, glucose, fructose, and polyethylene glycol (PEG); the second iron source includes one or two of ferric oxide and ferric oxalate.
[0018] Furthermore, in step S3, the ratio of the molar amount of the second iron source added to the molar amount of the iron phosphate is 1:(7-10); the second carbon source is glucose and polyethylene glycol; the ratio of the mass of the added glucose to the mass of the iron phosphate is (1-6):100, and the ratio of the mass of the added polyethylene glycol to the mass of the iron phosphate is (1-4):100.
[0019] Furthermore, in step S3, the lithium source includes two or three of lithium carbonate, lithium dihydrogen phosphate, and lithium phosphate.
[0020] Furthermore, in step S3, the molar ratio of total lithium elements to total iron elements in the mixture is (1.01-1.04):1.
[0021] Furthermore, in step S3, the lithium source includes lithium carbonate and lithium dihydrogen phosphate; and the molar ratio of the lithium carbonate to the lithium dihydrogen phosphate is 2:1.
[0022] The present invention also discloses a lithium iron phosphate material, which is prepared by the preparation method described above; the powder internal resistance of the lithium iron phosphate material is ≤8Ω.cm; the content of carbon element is <1.0wt%; the compaction density of the positive electrode sheet made of the lithium iron phosphate material is >3.0g / cm 3 .
[0023] The present invention also discloses an application of a lithium iron phosphate material, such as the lithium iron phosphate material described above is applied to the preparation of a lithium ion battery.
[0024] The present invention provides a method for preparing a lithium iron phosphate material, which improves the conductivity of the iron phosphate itself by in-situ doping with a carbon source with high conductivity during the synthesis of the iron phosphate, while reducing the coating amount of the second carbon source, thereby providing the conductivity of the lithium iron phosphate material while reducing the total carbon content in the lithium iron phosphate material, thereby improving the compaction density of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a scanning electron microscope image of the iron phosphate prepared in Example 1 of the present invention;
[0026] Figure 2 This is a scanning electron microscope image of the lithium iron phosphate material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0028] Example 1
[0029] Preparation of lithium iron phosphate material:
[0030] S1: In a reactor, ferrous sulfate is dissolved in phosphoric acid (the molar ratio of phosphoric acid to ferrous sulfate is 1.1:1), a high conductivity carbon source - multi-walled carbon nanotubes is added, the ratio of the mass of the added multi-walled carbon nanotubes to the mass of ferrous sulfate is 1:0.002, the divalent iron is oxidized to trivalent iron with H2O2, and then the pH of the reaction solution is adjusted to 2.0 with sodium hydroxide, the reaction temperature is 90°C, and the reaction obtains a mixed high conductivity carbon iron phosphate precipitate.
[0031] S2: The reactant was aged at 120° C. for 5 h, filtered, the obtained precipitate was washed with deionized water, dried, and the precipitate was placed in a muffle furnace and calcined at 650° C. for 3 h to obtain iron phosphate.
[0032] S3: The molar ratio of ferric phosphate to ferric oxide is 9:1; the molar ratio of lithium to iron is 1.03:1; the molar ratio of lithium carbonate to lithium dihydrogen phosphate is 2:1; the mass ratio of glucose to ferric phosphate is 0.04:1, and the mass ratio of PEG to ferric phosphate is 0.04:1. Add ferric phosphate, ferric oxide, lithium carbonate, lithium dihydrogen phosphate, glucose, and PEG to deionized water (solid-liquid ratio is 1:3), load the mixture into a ball mill, grind until the D100 of the solid particles in the mixture reaches 50 μm, transfer the mixture to a sand mill, stop sand milling until the D50 of the solid particles in the mixture is 350 nm, spray dry, and obtain a solid material.
[0033] S4: The obtained solid material is placed in a tubular furnace, heated to 780°C at a heating rate of 2.5°C / min under a nitrogen atmosphere, kept warm for 12 hours, and then cooled to room temperature at a cooling rate of 1.0°C / min to obtain a high-power and high-energy-density lithium iron phosphate material.
[0034] The prepared iron phosphate and lithium iron phosphate were examined by scanning electron microscopy to observe the morphological characteristics of the prepared materials. The results are as follows Figure 1-Figure 2 As shown. Figure 1 As shown in the figure, it can be clearly seen that multi-walled carbon nanotubes are distributed on the surface and end faces of the iron phosphate particles, indicating that the iron phosphate prepared in Example 1 has been effectively doped with high-conductivity carbon. Figure 2 As shown in the figure, two types of lithium iron phosphate morphologies can be seen, a large and relatively regular ellipsoid and a small and irregular polygon, which come from iron phosphate and ferric oxide respectively. At the same time, a small amount of multi-walled carbon nanotubes can still be seen distributed on the surface and end face of the lithium iron phosphate.
[0035] Example 2
[0036] Preparation of lithium iron phosphate material:
[0037] The difference between Example 2 and Example 1 is that the mass ratio of ferrous sulfate to multi-walled carbon nanotubes is 1:0.001, the mass ratio of glucose to ferric phosphate is 0.06:1, and the other steps are the same.
[0038] Comparative Example 1
[0039] 1. Dissolve ferrous sulfate in phosphoric acid (the molar ratio of phosphoric acid to ferrous sulfate is 1.1:1), oxidize the divalent iron to trivalent iron with H2O2, and then adjust the pH of the reaction solution to 2.0 with sodium hydroxide and the reaction temperature to 90°C to obtain iron phosphate precipitation.
[0040] 2. The reactant was aged at 120°C for 5 h, filtered, the precipitate was washed with deionized water, dried, and the precipitate was placed in a muffle furnace and calcined at 650°C for 3 h to obtain iron phosphate.
[0041] 3. According to the molar ratio of lithium to iron being 1.03, the mass ratio of glucose to iron phosphate being 0.08:1, and the mass ratio of PEG to iron phosphate being 0.04:1, iron phosphate, lithium carbonate, glucose, and PEG are added to deionized water (solid-liquid ratio being 1:3), the mixture is charged into a ball mill, and ground until the D100 of the solid particles in the mixture reaches within 50 μm, the mixture is transferred to a sand mill, and the sand milling is stopped when the D50 of the solid particles in the mixture is 350 nm, and the solid material is obtained by spray drying.
[0042] 4. The obtained solid material was placed in a tubular furnace, heated to 780°C at a heating rate of 1.3°C / min under a nitrogen atmosphere, kept warm for 12 hours, and then cooled to room temperature at a cooling rate of 1.3°C / min to obtain a lithium iron phosphate material.
[0043] Comparative Example 2
[0044] The difference between Comparative Example 2 and Example 1 is that ferric oxide is not added, the lithium source is lithium carbonate, the mass ratio of glucose to iron phosphate is 0.08:1, and the heating and cooling rates of the sintering program in step S4 are both changed to 1.3°C / min.
[0045] Performance Testing:
[0046] The physical properties of the synthetic iron phosphate of Examples 1-2 and Comparative Example 1 and the conventional commercially available Yacheng A100 iron phosphate were tested, and the results are shown in Table 1. D10, D50, D90, and Dmax correspond to the particle sizes of iron phosphate particles with a particle size volume ratio of 10%, 50%, 90%, and 97%, respectively, and are obtained by testing with a laser particle size analyzer. The specific surface area is tested using a specific surface area tester and a nitrogen adsorption method, and then the value obtained by fitting using the BET formula is used to characterize the total surface area per unit weight of the material.
[0047] Table 1 Physical property test results of iron phosphate prepared in the examples and comparative examples and commercially available iron phosphate
[0048]
[0049] As shown in Table 1, the corresponding D10, D50, and D90 of the iron phosphate to which a high-conductivity carbon source is added are generally higher than those of Yacheng A100 and Comparative Example 1, and as the amount of high-performance carbon added decreases, its particle size distribution is closer to that of A100 and Comparative Example 1, and the added high-conductivity carbon source does not cause a significant increase in the Dmax of the iron phosphate, indicating that the addition of a high-conductivity carbon source will not affect the subsequent processing of the iron phosphate. The specific surface area of the iron phosphate decreases with the decrease in the amount of the high-conductivity carbon source added. When the addition ratio is reduced to 1:0.001, the iron phosphate prepared is close to Comparative Example 1 and Yacheng A100. The tap density is negatively correlated with the amount of the high-conductivity carbon source added, and increases with the decrease in the amount added. Example 2 is close to Comparative Example 1 and Yacheng A100. The internal resistance of the powder is the value obtained by testing with a powder internal resistance meter under a pressure of 12t. When the high-conductivity carbon source addition ratio is 1:0.002, the powder internal resistance of the iron phosphate reaches (10 6 ~10 7 )Ω.cm, while the internal resistance of A100 and comparative example 1 powders exceeded the maximum range of the equipment by 10 9 Ω.cm, with the decrease of the amount of high conductivity carbon source added, the internal resistance index of iron phosphate powder increases.
[0050] The physical properties of Examples 1-2, Comparative Examples 1-2 and the commercially available product Yuneng Y9 were tested, and they were assembled into a button to test the electrical performance. The test results are shown in Table 2.
[0051] Button battery assembly method: lithium iron phosphate, conductive carbon SP, and adhesive PVDF (polyvinylidene fluoride) are added to the solvent NMP (N-methylpyrrolidone) in a mass ratio of 8:1:1 to prepare a slurry with a solid content of 30%, and use a coater to apply a 200μm thick coating on a 16μm aluminum foil, and then put it into a vacuum drying oven. After drying at 110°C for 2h, take out the circular positive electrode sheet punched into a diameter of 16mm, and put the positive electrode sheet*1, diaphragm*1, lithium sheet*1, gasket*1 and spring sheet*1 into the positive electrode shell in turn, drip 10 drops of lithium-ion battery electrolyte, cover the negative electrode shell, and seal it with a sealing machine.
[0052] Test method: Take the assembled battery in the voltage range of 2.5-3.9V, first charge it with 0.1C constant current to 3.9V, then switch to constant voltage charging until the current drops to 0.05C, let it stand for 5 minutes, discharge it with 0.1C constant current to 2.5V, let it stand for 5 minutes, and record the discharge capacity in grams C-0.1. Continue to charge it with 1C constant current to 3.9V, switch to constant voltage charging until the current drops to 0.05C, let it stand for 5 minutes, discharge it with 1C constant current to 2.5V, let it stand for 5 minutes, and record the discharge capacity in grams C-1. Continue to charge it with 3C constant current to 3.9V, switch to constant voltage charging until the current drops to 0.05C, let it stand for 5 minutes, discharge it with 3C constant current to 2.5V, let it stand for 5 minutes, and record the discharge capacity in grams C-3.
[0053] Table 2 Performance test results of the embodiment, comparative example and commercially available lithium iron phosphate
[0054]
[0055] As shown in Table 2, the 0.1C, 1C and 3C gram capacities of the lithium iron phosphate prepared by doping with a high conductivity carbon source in Example 1 and Example 2 are all higher than the corresponding values of the commercially available Yuneng Y9, Comparative Example 1 and Comparative Example 2. The 0.1C discharge gram capacity of the lithium iron phosphate prepared in Example 1 reaches 162.4 mAh / g, the 1C discharge gram capacity is 150.7 mAh / g, and the 3C discharge gram capacity is 141.2 mAh / g. The corresponding pole piece compaction density of Example 1 and Example 2 reaches 3.01 g / cm 3 This is much higher than the 2.48 g / cm2 of commercial products. 3 And Comparative Example 1 and Comparative Example 2.
[0056] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lithium iron phosphate material, characterized in that: The following steps are involved: S1: Mix the first iron source, high conductivity carbon source, and phosphoric acid, add an oxidant to remove Fe 2+ Oxidized to Fe 3+ , then add a pH regulator to adjust the pH of the reaction solution to 1.2-2.5, and control the temperature at 85-95°C until the reaction is complete; S2: maintaining the temperature of the reaction solution at 110-130° C. for aging for 3-5 hours, separating the obtained precipitate, washing, drying, and calcining at 550-700° C. to obtain iron phosphate; S3: mixing the iron phosphate, the second carbon source, the lithium source, the second iron source and water to form a mixture; controlling the particle size of solid particles in the mixture to D50 of 200-400 nm by ball milling and sand milling; spray drying the mixture to obtain a solid; S4: In a protective gas atmosphere, heat the solid to 730-790°C at a heating rate of 1.5-5°C / min, keep warm for 6-12 hours, and cool to obtain a lithium iron phosphate material.
2. The method for preparing a lithium iron phosphate material according to claim 1, characterized in that: In step S1, the first iron source includes one or more of ferrous sulfate, ferric sulfate, elemental iron, and ferric chloride; the high conductivity carbon source includes one or more of porous nanocarbon, acetylene black, superconducting carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, 3D graphene mesh, nanographene sheets, and carbon fibers.
3. The method for preparing a lithium iron phosphate material according to claim 2, characterized in that: In step S1, the molar ratio of the iron element in the first iron source to the phosphorus element in the phosphoric acid is 1:1.0-1.2; the mass ratio of the first iron source to the first carbon source is 1:0.0005-0.
005.
4. The method for preparing a lithium iron phosphate material according to claim 1, characterized in that: In step S3, the second carbon source includes two or more of sucrose, glucose, fructose, and polyethylene glycol; the second iron source includes one or two of ferric oxide and ferric oxalate.
5. The method for preparing a lithium iron phosphate material according to claim 4, characterized in that: In step S3, the ratio of the molar amount of the second iron source added to the molar amount of the iron phosphate is 1:7-10; the second carbon source is glucose and polyethylene glycol; the mass ratio of the added glucose to the iron phosphate is 1-6:100, and the mass ratio of the added polyethylene glycol to the iron phosphate is 1-4:
100.
6. The method for preparing a lithium iron phosphate material according to claim 5, characterized in that: In step S3, the lithium source includes two or three of lithium carbonate, lithium dihydrogen phosphate, and lithium phosphate.
7. The method for preparing a lithium iron phosphate material according to claim 6, characterized in that: In step S3, in the mixture, the molar ratio of total lithium elements to total iron elements is 1.01-1.04:
1.
8. The method for preparing a lithium iron phosphate material according to claim 6, characterized in that: In the step S3, the lithium source includes lithium carbonate and lithium dihydrogen phosphate; the molar ratio of the lithium carbonate to the lithium dihydrogen phosphate is 2:
1.
9. A lithium iron phosphate material, characterized in that: Prepared by the preparation method described in any one of claims 1-8; the powder internal resistance of the lithium iron phosphate material is ≤8Ω.cm; the content of carbon element is <1.0wt%; the compaction density of the positive electrode sheet made of the lithium iron phosphate material is >3.0g / cm 3 .
10. An application of lithium iron phosphate material, characterized in that: The lithium iron phosphate material as claimed in claim 9 is used in the preparation of lithium-ion batteries.